Enhancing CGIAR collaboration: Mainstreaming PABRA’s food corridors approach for better diets and nutrition impacts - Buruchara, Robin; Munthali, Justice; Chideya, Yohane; Rubyogo, Jean Claude (2025)
Improving diets is essential to achieving key Sustainable Development Goals (SDGs), addressing all forms of malnutrition, and advancing agriculture, health, gender equity, and climate action. The CGIAR Better Diets and Nutrition (BDN) Science Program positions diet quality at the center of its 2030 Research Portfolio, emphasizing diverse, nutrient-rich, and safe foods across food groups. During a CGIAR Science Week 2025 side event, over 20 stakeholders examined how agricultural innovation can unlock better diets through the BDN program. Participants emphasized stronger cross-center collaboration, coherent agriculture-to-nutrition strategies, and a community of practice to translate evidence into actionable nutrition outcomes. Priority strategies discussed included nutrition-sensitive agricultural research, harmonized MEAL systems, market and policy engagement, value-chain and corridor models, innovation support, and scaling context-specific solutions such as homegrown school feeding. A shared commitment emerged to systematically integrate nutrition across CGIAR initiatives and leverage collective resources for greater impact. The Pan-Africa Bean Research Alliance (PABRA) Bean Commodity Corridor Model illustrates this approach by linking breeding, seed systems, value addition, market innovation, and policy alignment across 31 countries. Reaching millions of value-chain actors, it demonstrates how integrated research can drive equitable, sustainable dietary improvements and advance nutrition-related SDGs across diverse food systems.